Editorial - Deniz Evcik (Archives of Rheumatology, 2011)
Dear Readers of the Turkish Journal of Rheumatology, It is a great pleasure to introduce you to the first issue of this year. In this issue of the TJR, there are thirteen interesting articles. I would like to thank all who contributed to the 9th Symposium of Rheumatology held between 10-13 March 2011 in Antalya. Special thanks to the organizing committee for its successful, high-quality scientific organization with international guest lecturers. The Turkish League Against Rheumatism continues to proceed with its scientific activity. TLAR Ankylosing Spondylitis and Rheumatoid Arthritis study groups have recently published their registry results. Moreover, it would be a pleasure to introduce new database called as the “Early arthritis registry” system within TLAR. We hope many physicians will contribute their data to this registry system and that this database will provide valuable scientific information about early arthritis in our country. The TJR has changed its publisher and from now on Bayçınar Medical Publishing will assist us with the publication service. This year the TJR’s policy is rapid manuscript review and rapid online publication. Our expectation is to reduce delayed publishing. Finally, I hope the TJR will become a high-impact international journal in the near future with your valuable scientific contributions. As a reminder, you can easily use our journal’s web search page for access to our previous publications. Thank you. With my best regards Prof. Dr. Deniz Evcik Editor